Necrotizing Fasciitis Caused by Aeromonas hydrophila With Catastrophic Progression. (December 2021) - Huang, Dun-Wei; Liu, Hung-Hui; Dai, Niann-Tzyy; Chen, Shyi-Gen; Tzeng, Yuan-Sheng
Necrotizing fasciitis is a severe deep soft tissue infection with poor disease prognosis. The Aeromonas species is characterized as gram-negative, facultative, anaerobic small bacilli that are ubiquitously distributed in aquatic environments. Necrotizing fasciitis caused by this species is rare but has an extremely high mortality rate, especially in immunocompromised individuals. This study presents the case of a 39-year-old man with alcoholic liver cirrhosis, Child-Pugh class B, with necrotizing fasciitis caused by Aeromonas hydrophila . Despite debridement and bilateral above-knee amputation performed immediately, rapid progression to bilateral upper limbs and trunk was noted in 24 hours. The patient expired from septic shock with multiple organ failure in less than 48 hours following initial presentation. Two similar cases with different medical intervention and results have been reported in the literature and are further discussed in the present study. This allows the authors to suggest potential solutions for an improved clinical outcome.